KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA PADA MATERI RELASI DAN FUNGSI - Anggraeni, Dewi; Ramlah, Ramlah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The purpose of this study was to describe the extent of mathematical critical thinking skills of junior high school students on the material of relations and functions. The research method used is a descriptive qualitative approach involving 3 students from 39 students of class VIII SMPN 3 Cihampelas as research subjects. Data was collected through giving test questions related to relation and function material and interviews to gain in-depth understanding. Based on the results of this study, it can be concluded that students' mathematical critical thinking skills in relation and function material can be classified as quite good. This can be seen from the number of students who are in the medium category. While some others are in the high and low categories. Students who have high mathematical critical thinking skills can fulfill all five indicators of mathematical critical thinking, namely elementery clarification, basic support, advance clarification, strategy and tactic, inference. Students in the medium category were only unable to fulfill the inference indicator, while students in the low category were only able to fulfill the elementary clarification indicator.